(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The demand for adequate security to electronic data system grows high over the decades. Security is the one of the biggest concern in different type of networks. Due to diversify nature of network, security breaching became a common issue in different form of networks. Solutions for network security comes with concepts like cryptography in which distribution of keys have been done. Encryption and key generation became a vital tool for preventing the threats to data sharing and tool to preserve the data integrity so we are focusing on security enhancing by enhancing the level of encryption in network. This study’s main goal is to reflect the importance of security in network and provide the better encryption technique for currently implemented encryption techniques in simple and powerful method. In our research we have proposed a modular 37 and select any number and calculate inverse of the selected integer using modular 37. The symmetric key distribution should be done in the secured manner. Also, we examine the performance of our new SSK algorithm with other existing symmetric key algorithm.